Preparation method and application of modified composite Ti3C2 lithium battery negative electrode material

By preparing porous Ti3C2/MnO2 composite materials, the problem of Ti3C2 nanosheets aggregation and stacking in electrochemical reactions is solved, the electrochemical performance and mechanical stability of lithium batteries are improved, and the service life is extended.

CN120535012APending Publication Date: 2025-08-26广西华政新能源科技有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510658674.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-21
Publication Date
2025-08-26

AI Technical Summary

Technical Problem

Ti3C2 nanosheets are prone to aggregation and stacking during electrochemical reactions, resulting in the loss of ion adsorption sites, the increase of ion diffusion impedance, and the device performance is reduced.

Method used

Porous Ti3C2 nanosheets were prepared by chemical etching, and nano MnO2 was grown in situ on the surface of the porous Ti3C2 nanosheets by aqueous tungsten disulfide solution treatment and potassium permanganate combined with ethanol heat to form a porous Ti3C2/MnO2 composite material, forming a three-dimensional conductive network interconnection to improve the specific surface area and conductive properties of the material.

Benefits of technology

It effectively solves the aggregation and stacking problems between Ti3C2 sheets, improves the electrochemical performance and mechanical stability of lithium batteries, and enhances the safety and service life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005413175500000101
    Figure BDA0005413175500000101
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a modified composite Ti3C2 lithium battery negative electrode material, and belongs to the technical field of lithium batteries. The preparation method comprises the following steps: (1) preparing a porous Ti3C2 nanosheet; (2) preparing a modified porous Ti3C2 material; (3) dispersing the porous Ti3C2 nanosheets in a potassium permanganate aqueous solution, then adding ethanol for reaction, and after the reaction is finished, cleaning and drying a reaction product through a vacuum filtration method to obtain a porous Ti3C2 / MnO2 composite material; and (4) mixing the modified porous Ti3C2 material with the porous Ti3C2 / MnO2 composite material to obtain the modified composite Ti3C2 lithium battery negative electrode material. According to the invention, the problem that the Ti3C2 nanosheets are easy to aggregate and stack in the electrochemical reaction process can be effectively solved, and the purpose of improving the electrochemical performance of the Ti3C2 lithium battery is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium batteries, and in particular to a preparation method and application of a modified composite Ti3C2 lithium battery negative electrode material. Background Art

[0002] With the rapid development of portable electronics and power equipment, demands for higher performance from lithium-ion batteries are increasing. Graphite, with its high theoretical capacity and excellent conductivity, has become the mainstream anode material for lithium-ion batteries. However, the risk of "lithium plating" caused by uneven deposition of lithium ions on the graphite surface significantly reduces battery safety. Therefore, the search for new lithium-ion battery anode materials to replace graphite is of great research significance.

[0003] MXene materials are among the most popular two-dimensional nanomaterials after graphene. As active materials in supercapacitors, they exhibit ultrahigh volumetric capacitance. They offer excellent rate capability as negative electrodes for lithium-, sodium-, and potassium-ion batteries, and significantly improve the cycling performance of lithium-sulfur batteries. Furthermore, MXene can be easily fabricated into flexible, integrated membrane electrodes, enabling applications in flexible wearable energy storage devices. MXene materials have rapidly developed in recent years and have become a leading research topic in the lithium battery field. Ti3C2 is currently the most extensively and intensively studied MXene material.

[0004] As an emerging electrode material, Ti3C2 has been widely studied both domestically and internationally, but the problem of Ti3C2's easy aggregation and stacking remains unresolved. Although Ti3C2 has metallic conductivity, strong chemical adsorption capacity, and structural diversity, which helps improve the conductivity of Ti3C2 lithium batteries and thus improve the overall performance of the battery, Ti3C2 is prone to aggregation and stacking during the electrochemical reaction process, resulting in the loss of ion adsorption sites, increased ion diffusion impedance, and reduced device performance. Therefore, how to effectively slow down the stacking of Ti3C2 nanosheets and modify the Ti3C2 lithium-ion battery negative electrode material is particularly important for improving the battery's electrochemical performance and mechanical stability. Summary of the Invention

[0005] The present invention aims to address the aforementioned issues with the prior art by providing a method for preparing a modified composite Ti3C2 lithium battery negative electrode material and its application. This invention effectively addresses the problem of Ti3C2 nanosheets easily aggregating and stacking during electrochemical reactions, thereby improving the electrochemical performance of Ti3C2 lithium batteries.

[0006] In order to achieve the above object, the technical solution of the present invention is as follows:

[0007] A method for preparing a modified composite Ti3C2 lithium battery negative electrode material comprises the following steps:

[0008] (1) Preparation of porous Ti3C2 nanosheets: Ti3C2 was first prepared by chemical etching, then stirred with tetramethylammonium hydroxide solution, and dried to obtain porous Ti3C2 nanosheets;

[0009] (2) Preparation of modified porous Ti3C2 material: adding tungsten disulfide powder to a polyethyleneimine aqueous solution, ultrasonicating, and centrifuging to obtain treated tungsten disulfide, and adding the treated tungsten disulfide to water to obtain a tungsten disulfide aqueous solution; adding the Ti3C2 nanosheets obtained in step (1) to the tungsten disulfide aqueous solution, stirring, and drying to obtain a modified porous Ti3C2 material;

[0010] (3) Preparation of porous Ti3C2 / MnO2 composite material: The porous Ti3C2 nanosheets obtained in step (1) are dispersed in a potassium permanganate aqueous solution in a reactor, ethanol is added to the reactor, and the temperature is raised to 75-100°C for reaction. After the reaction is completed, the reaction product is cleaned by vacuum filtration and dried to obtain a porous Ti3C2 / MnO2 composite material;

[0011] (4) Preparation of modified composite Ti3C2 lithium battery negative electrode material: The modified porous Ti3C2 material prepared in step (2) is mixed with the porous Ti3C2 / MnO2 composite material prepared in step (3) to obtain a modified composite Ti3C2 lithium battery negative electrode material.

[0012] Furthermore, step (1) specifically includes the following steps: adding Ti3AlC2 to an acidic LiF etching solution, heating to 38-45°C, reacting for 20-30 hours, collecting Ti3C2, making Ti3C2 into a suspension, adding a tetramethylammonium hydroxide solution with a mass concentration of 20-30% to the Ti3C2 suspension and stirring, stirring and reacting at 38-45°C for 48-60 hours, collecting and drying to obtain porous Ti3C2 nanosheets.

[0013] Furthermore, step (2) specifically includes the following steps: adding 1-2 g of tungsten disulfide powder to 100 mL of a polyethyleneimine aqueous solution with a mass concentration of 1-3%, treating it at an ultrasonic power of 100-150 W for 6-10 hours, centrifuging, and drying to obtain treated tungsten disulfide, adding the treated tungsten dioxide to water and mixing to obtain a tungsten disulfide aqueous solution, adding the Ti3C2 nanosheets obtained in step (1) to the tungsten disulfide aqueous solution, wherein the mass ratio of the Ti3C2 nanosheets to the treated tungsten dioxide is 1-5:2-8, stirring for 5-8 hours, centrifuging, and drying to obtain a modified porous Ti3C2 material.

[0014] Furthermore, in step (3), the concentration of the potassium permanganate aqueous solution is 4-8wt%, the mass ratio of potassium permanganate to the ethanol is 3.8-4.5:1, and the addition ratio of the porous Ti3C2 nanosheets to the ethanol is 0.05-0.3g:100mL.

[0015] Furthermore, in step (3), the reaction is carried out in the following three stages:

[0016] Stage 1: Stirring reaction at 75-80°C for 1-2 hours;

[0017] The second stage: ultrasonic reaction, power is 300-400w, temperature is 90-100℃, time is 1-2h;

[0018] The third stage: stirring reaction, the temperature is 80-90℃, and the time is 3-5h.

[0019] Furthermore, in step (4), the mass ratio of the modified porous Ti3C2 material to the porous Ti3C2 / MnO2 composite material is 1-5:20-80.

[0020] The present invention also provides an application of the modified composite Ti3C2 lithium battery negative electrode material prepared by the above preparation method in a lithium battery, specifically using the modified composite Ti3C2 lithium battery negative electrode material as the negative electrode material of the lithium battery.

[0021] The beneficial effects of the present invention are as follows:

[0022] The present invention uses porous Ti3C2 nanosheets as a substrate and prepares a modified porous Ti3C2 material by treating it with a tungsten disulfide aqueous solution. At the same time, potassium permanganate combined with an ethanol thermal method is used to in situ grow nano-MnO2 on the surface of the porous Ti3C2 nanosheets to prepare a porous Ti3C2 / MnO2 composite material. This material forms a porous conductive structure with a three-dimensional conductive network interconnection. At the same time, a synergistic effect is formed with the MnO2 interspersed therein, effectively increasing the material's specific surface area and conductivity. The modified porous Ti3C2 material combined with the porous Ti3C2 / MnO2 composite material has excellent area-to-capacity, effectively improving the battery's energy storage and endurance, and enhancing the battery's safety and service life. The modified composite Ti3C2 lithium battery negative electrode material prepared by the present invention has excellent conductivity, mechanical properties, and thermal stability, effectively improving the battery's electrochemical performance. The present invention can effectively solve the technical problems of aggregation and stacking between existing Ti3C2 sheets, give full play to the electrochemical properties of the Ti3C2 sheets, effectively increase the specific capacity of the electrode, and extend the service life. DETAILED DESCRIPTION

[0023] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention will be further described in detail below in conjunction with specific embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0024] Example 1

[0025] A method for preparing a modified composite Ti3C2 lithium battery negative electrode material comprises the following steps:

[0026] (1) Preparation of porous Ti3C2 nanosheets: Ti3AlC2 was slowly added to the acidic LiF etching solution. To prevent the addition speed from being too fast, which would cause local overheating and oxidation of the material, the temperature in the reactor was raised to 40°C. After reacting for 24 hours, Ti3C2 was collected and suspended in 100 mL of water. 60 mL of a 25% aqueous solution of tetramethylammonium hydroxide was added to the Ti3C2 suspension and stirred. The mixture was stirred at 40°C for 48 hours, and the porous Ti3C2 nanosheets were obtained by collection and drying.

[0027] (2) Preparation of modified porous Ti3C2 materials:

[0028] 1.5 g of tungsten disulfide powder was added to 100 mL of a 2% polyethyleneimine aqueous solution, and the mixture was treated at 120 W ultrasonic power for 8 h, centrifuged, and dried to obtain the treated tungsten disulfide. The treated tungsten dioxide was added to water and mixed to obtain a tungsten disulfide aqueous solution. The Ti3C2 nanosheets obtained in step (1) were added to the tungsten disulfide aqueous solution, with the mass ratio of the Ti3C2 nanosheets to the treated tungsten dioxide being 5:3. The mixture was stirred for 6 h, centrifuged, and dried to obtain a modified porous Ti3C2 material.

[0029] (3) Preparation of porous Ti3C2 / MnO2 composite material: The porous Ti3C2 nanosheets obtained in step (1) were dispersed in a 6wt% potassium permanganate aqueous solution in a reactor. Ethanol was then added to the reactor and the temperature was raised. A first stage of stirring reaction was performed at 80°C for 1 hour. A second stage of ultrasonic reaction was performed at a power of 350W, a temperature of 95°C for 2 hours. Finally, a third stage of stirring reaction was performed at 85°C for 4 hours. After the reaction was completed, the reaction product was cleaned by vacuum filtration and dried to obtain a porous Ti3C2 / MnO2 composite material. The mass ratio of potassium permanganate to the ethanol was 4:1, and the addition ratio of the porous Ti3C2 nanosheets to the ethanol was 0.1g:100mL.

[0030] (4) Preparation of modified composite Ti3C2 lithium battery negative electrode material: The modified porous Ti3C2 material prepared in step (2) and the porous Ti3C2 / MnO2 composite material prepared in step (3) are mixed in a mass ratio of 2:60 to obtain a modified composite Ti3C2 lithium battery negative electrode material.

[0031] Example 2

[0032] A method for preparing a modified composite Ti3C2 lithium battery negative electrode material comprises the following steps:

[0033] (1) Preparation of porous Ti3C2 nanosheets: Ti3AlC2 was added to an acidic LiF etching solution, heated to 45°C, and Ti3C2 was collected after reaction for 20 h. 2 g of Ti3C2 was prepared into a suspension with 100 mL of water. 40 mL of a 30% mass concentration of tetramethylammonium hydroxide solution was added to the Ti3C2 suspension and stirred. The reaction was stirred at 45°C for 48 h, and the porous Ti3C2 nanosheets were obtained by collection and drying.

[0034] (2) Preparation of modified porous Ti3C2 materials:

[0035] 1 g of tungsten disulfide powder was added to 100 mL of a 1% polyethyleneimine aqueous solution, and the mixture was treated at 150 W ultrasonic power for 6 h, centrifuged, and dried to obtain the treated tungsten disulfide. The treated tungsten dioxide was added to water and mixed to obtain a tungsten disulfide aqueous solution. The Ti3C2 nanosheets obtained in step (1) were added to the tungsten disulfide aqueous solution, with the mass ratio of the Ti3C2 nanosheets to the treated tungsten dioxide being 1:1. The mixture was stirred for 5 h, centrifuged, and dried to obtain a modified porous Ti3C2 material.

[0036] (3) Preparation of porous Ti3C2 / MnO2 composite material: The porous Ti3C2 nanosheets obtained in step (1) were dispersed in a 5wt% potassium permanganate aqueous solution in a reactor. Ethanol was then added to the reactor and the temperature was raised. A first stage of stirring reaction was performed at a temperature of 75°C for 2 hours. A second stage of ultrasonic reaction was performed at a power of 400w, a temperature of 90°C for 2 hours. Finally, a third stage of stirring reaction was performed at a temperature of 80°C for 5 hours. After the reaction was completed, the reaction product was cleaned by vacuum filtration and dried to obtain a porous Ti3C2 / MnO2 composite material. The mass ratio of potassium permanganate to the ethanol was 4.2:1, and the addition ratio of the porous Ti3C2 nanosheets to the ethanol was 0.08g:100mL.

[0037] (4) Preparation of modified composite Ti3C2 lithium battery negative electrode material: The modified porous Ti3C2 material prepared in step (2) and the porous Ti3C2 / MnO2 composite material prepared in step (3) are mixed in a mass ratio of 4:70 to obtain a modified composite Ti3C2 lithium battery negative electrode material.

[0038] Example 3

[0039] A method for preparing a modified composite Ti3C2 lithium battery negative electrode material comprises the following steps:

[0040] (1) Preparation of porous Ti3C2 nanosheets: Ti3AlC2 was added to an acidic LiF etching solution, heated to 38°C, and Ti3C2 was collected after reaction for 30 h. 2 g of Ti3C2 was prepared into a suspension with 100 mL of water. 50 mL of a 25% tetramethylammonium hydroxide solution was added to the Ti3C2 suspension and stirred. The mixture was stirred at 38°C for 60 h, and the porous Ti3C2 nanosheets were obtained by collection and drying.

[0041] (2) Preparation of modified porous Ti3C2 materials:

[0042] 2 g of tungsten disulfide powder was added to 100 mL of a 3% polyethyleneimine aqueous solution, and the mixture was treated at 100 W ultrasonic power for 10 h, centrifuged, and dried to obtain the treated tungsten disulfide. The treated tungsten dioxide was added to water and mixed to obtain a tungsten disulfide aqueous solution. The Ti3C2 nanosheets obtained in step (1) were added to the tungsten disulfide aqueous solution, with the mass ratio of the Ti3C2 nanosheets to the treated tungsten dioxide being 5:8. The mixture was stirred for 8 h, centrifuged, and dried to obtain a modified porous Ti3C2 material.

[0043] (3) Preparation of porous Ti3C2 / MnO2 composite material: The porous Ti3C2 nanosheets obtained in step (1) were dispersed in a 6wt% potassium permanganate aqueous solution in a reactor. Ethanol was then added to the reactor and the temperature was raised. A first stage of stirring reaction was performed at a temperature of 78°C for 1.5 hours. A second stage of ultrasonic reaction was performed at a power of 300w, a temperature of 100°C for 1 hour. Finally, a third stage of stirring reaction was performed at a temperature of 85°C for 5 hours. After the reaction was completed, the reaction product was cleaned by vacuum filtration and dried to obtain a porous Ti3C2 / MnO2 composite material. The concentration of the potassium permanganate aqueous solution was such that the mass ratio of potassium permanganate to the ethanol was 3.8:1. The addition ratio of the porous Ti3C2 nanosheets to the ethanol was 0.2g:100mL.

[0044] (4) Preparation of modified composite Ti3C2 lithium battery negative electrode material: The modified porous Ti3C2 material prepared in step (2) and the porous Ti3C2 / MnO2 composite material prepared in step (3) are mixed in a mass ratio of 1:40 to obtain a modified composite Ti3C2 lithium battery negative electrode material.

[0045] Example 4

[0046] A method for preparing a modified composite Ti3C2 lithium battery negative electrode material comprises the following steps:

[0047] (1) Preparation of porous Ti3C2 nanosheets: Ti3AlC2 was added to an acidic LiF etching solution, heated to 40°C, and Ti3C2 was collected after reaction for 25 h. 2 g of Ti3C2 was prepared into a suspension with 100 mL of water. 80 mL of a 20% mass concentration tetramethylammonium hydroxide solution was added to the Ti3C2 suspension and stirred. The reaction was stirred at 40°C for 50 h, and the porous Ti3C2 nanosheets were obtained by collection and drying.

[0048] (2) Preparation of modified porous Ti3C2 materials:

[0049] 1.5 g of tungsten disulfide powder was added to 100 mL of a 2% polyethyleneimine aqueous solution, and the mixture was treated at 100 W ultrasonic power for 8 h, centrifuged, and dried to obtain the treated tungsten disulfide. The treated tungsten dioxide was added to water and mixed to obtain a tungsten disulfide aqueous solution. The Ti3C2 nanosheets obtained in step (1) were added to the tungsten disulfide aqueous solution, with the mass ratio of the Ti3C2 nanosheets to the treated tungsten dioxide being 4:3. The mixture was stirred for 7 h, centrifuged, and dried to obtain a modified porous Ti3C2 material.

[0050] (3) Preparation of porous Ti3C2 / MnO2 composite material: The porous Ti3C2 nanosheets obtained in step (1) were dispersed in an 8wt% potassium permanganate aqueous solution in a reactor. Ethanol was then added to the reactor and the temperature was raised. A first stage of stirring reaction was performed at 80°C for 1 hour. A second stage of ultrasonic reaction was performed at a power of 300w, a temperature of 95°C for 2 hours. Finally, a third stage of stirring reaction was performed at 80°C for 5 hours. After the reaction was completed, the reaction product was cleaned by vacuum filtration and dried to obtain a porous Ti3C2 / MnO2 composite material. The mass ratio of potassium permanganate to the ethanol was 4.5:1, and the addition ratio of the porous Ti3C2 nanosheets to the ethanol was 0.3g:100mL.

[0051] (4) Preparation of modified composite Ti3C2 lithium battery negative electrode material: The modified porous Ti3C2 material prepared in step (2) and the porous Ti3C2 / MnO2 composite material prepared in step (3) are mixed in a mass ratio of 5:80 to obtain a modified composite Ti3C2 lithium battery negative electrode material.

[0052] Comparative Example 1

[0053] A method for preparing a Ti3C2 lithium battery negative electrode material comprises the following steps:

[0054] Ti3AlC2 was slowly added to the acidic LiF etching solution. To prevent the addition speed from being too fast, which would cause local overheating and oxidation of the material, the temperature in the reactor was raised to 40°C. After reacting for 24 hours, Ti3C2 was collected and suspended with 100 mL of water. 60 mL of a 25% mass concentration of tetramethylammonium hydroxide aqueous solution was added to the Ti3C2 suspension and stirred. The reaction was stirred at 40°C for 48 hours. The porous Ti3C2 nanosheets were collected and dried to obtain the Ti3C2 lithium battery negative electrode material.

[0055] Comparative Example 2

[0056] A method for preparing a modified composite Ti3C2 lithium battery negative electrode material comprises the following steps:

[0057] (1) Preparation of porous Ti3C2 nanosheets: Ti3AlC2 was slowly added to the acidic LiF etching solution. To prevent the addition speed from being too fast, which would cause local overheating and oxidation of the material, the temperature in the reactor was raised to 40°C. After reacting for 24 hours, Ti3C2 was collected and suspended in 100 mL of water. 60 mL of a 25% aqueous solution of tetramethylammonium hydroxide was added to the Ti3C2 suspension and stirred. The mixture was stirred at 40°C for 48 hours, and the porous Ti3C2 nanosheets were obtained by collection and drying.

[0058] (2) Preparation of modified porous Ti3C2 materials:

[0059] 1.5 g of tungsten disulfide powder was added to 100 mL of a 2% polyethyleneimine aqueous solution, and the mixture was treated at 120 W ultrasonic power for 8 h, centrifuged, and dried to obtain the treated tungsten disulfide. The treated tungsten dioxide was added to water and mixed to obtain a tungsten disulfide aqueous solution. The Ti3C2 nanosheets obtained in step (1) were added to the tungsten disulfide aqueous solution, with the mass ratio of the Ti3C2 nanosheets to the treated tungsten dioxide being 5:3. The mixture was stirred for 6 h, centrifuged, and dried to obtain a modified porous Ti3C2 material.

[0060] (3) Preparation of porous Ti3C2 / MnO2 composite material: The porous Ti3C2 nanosheets obtained in step (1) were dispersed in water in a reactor, and MnO2 powder was added, wherein the mass ratio of the MnO2 to the porous Ti3C2 nanosheets was 1:10. The temperature was then raised, and a first-stage stirring reaction was performed at 80°C for 1 hour. A second-stage ultrasonic reaction was then performed at a power of 350W, a temperature of 95°C for 2 hours, and a third-stage stirring reaction was performed at 85°C for 4 hours. After the reaction was completed, the reaction product was cleaned by vacuum filtration and dried to obtain a porous Ti3C2 / MnO2 composite material, wherein the mass ratio of potassium permanganate to the ethanol was 4:1, and the addition ratio of the porous Ti3C2 nanosheets to the ethanol was 0.1g:100mL.

[0061] (4) Preparation of modified composite Ti3C2 lithium battery negative electrode material: The modified porous Ti3C2 material prepared in step (2) and the porous Ti3C2 / MnO2 composite material prepared in step (3) are mixed in a mass ratio of 2:60 to obtain a modified composite Ti3C2 lithium battery negative electrode material.

[0062] Comparative Example 3

[0063] A method for preparing a modified composite Ti3C2 lithium battery negative electrode material comprises the following steps:

[0064] (1) Preparation of porous Ti3C2 nanosheets: Ti3AlC2 was slowly added to the acidic LiF etching solution. To prevent the addition speed from being too fast, which would cause local overheating and oxidation of the material, the temperature in the reactor was raised to 40°C. After reacting for 24 hours, Ti3C2 was collected and suspended in 100 mL of water. 60 mL of a 25% aqueous solution of tetramethylammonium hydroxide was added to the Ti3C2 suspension and stirred. The mixture was stirred at 40°C for 48 hours, and the porous Ti3C2 nanosheets were obtained by collection and drying.

[0065] (2) Preparation of modified porous Ti3C2 materials:

[0066] 1.5 g of tungsten disulfide powder was added to 100 mL of a 2% polyethyleneimine aqueous solution, and the mixture was treated at 120 W ultrasonic power for 8 h, centrifuged, and dried to obtain the treated tungsten disulfide. The treated tungsten dioxide was added to water and mixed to obtain a tungsten disulfide aqueous solution. The Ti3C2 nanosheets obtained in step (1) were added to the tungsten disulfide aqueous solution, with the mass ratio of the Ti3C2 nanosheets to the treated tungsten dioxide being 5:3. The mixture was stirred for 6 h, centrifuged, and dried to obtain a modified porous Ti3C2 material.

[0067] (3) Preparation of porous Ti3C2 / MnO2 composite material: The porous Ti3C2 nanosheets obtained in step (1) were dispersed in a 6 wt% potassium permanganate aqueous solution in a reactor. Ethanol was then added to the reactor, and the temperature was raised to 95°C and stirred for 7 hours. After the reaction, the reaction product was cleaned by vacuum filtration and dried to obtain a porous Ti3C2 / MnO2 composite material; wherein the mass ratio of potassium permanganate to the ethanol was 4:1, and the ratio of the porous Ti3C2 nanosheets to the ethanol was 0.1 g:100 mL.

[0068] (4) Preparation of modified composite Ti3C2 lithium battery negative electrode material: The modified porous Ti3C2 material prepared in step (2) and the porous Ti3C2 / MnO2 composite material prepared in step (3) are mixed in a mass ratio of 2:60 to obtain a modified composite Ti3C2 lithium battery negative electrode material.

[0069] Comparative Example 4

[0070] A method for preparing a modified composite Ti3C2 lithium battery negative electrode material comprises the following steps:

[0071] (1) Preparation of porous Ti3C2 nanosheets: Ti3AlC2 was slowly added to the acidic LiF etching solution. To prevent the addition speed from being too fast, which would cause local overheating and oxidation of the material, the temperature in the reactor was raised to 40°C. After reacting for 24 hours, Ti3C2 was collected and suspended in 100 mL of water. 60 mL of a 25% aqueous solution of tetramethylammonium hydroxide was added to the Ti3C2 suspension and stirred. The mixture was stirred at 40°C for 48 hours, and the porous Ti3C2 nanosheets were obtained by collection and drying.

[0072] (2) Preparation of modified porous Ti3C2 materials:

[0073] 1.5 g of tungsten disulfide powder was added to 100 mL of a 2% polyethyleneimine aqueous solution, and the mixture was treated at 120 W ultrasonic power for 8 h, centrifuged, and dried to obtain the treated tungsten disulfide. The treated tungsten dioxide was added to water and mixed to obtain a tungsten disulfide aqueous solution. The Ti3C2 nanosheets obtained in step (1) were added to the tungsten disulfide aqueous solution, with the mass ratio of the Ti3C2 nanosheets to the treated tungsten dioxide being 5:3. The mixture was stirred for 6 h, centrifuged, and dried to obtain a modified porous Ti3C2 material.

[0074] (3) Preparation of porous Ti3C2 / MnO2 composite material: The porous Ti3C2 nanosheets obtained in step (1) were dispersed in a 6wt% potassium permanganate aqueous solution in a reactor. Ethanol was then added to the reactor and the temperature was raised. A first stage of ultrasonic reaction was performed at a power of 350W, a temperature of 80°C, and a time of 1 hour. A second stage of stirring reaction was performed at a temperature of 90°C and a time of 2 hours. Finally, a third stage of stirring reaction was performed at a temperature of 100°C and a time of 4 hours. After the reaction was completed, the reaction product was cleaned by vacuum filtration and dried to obtain a porous Ti3C2 / MnO2 composite material; wherein the mass ratio of potassium permanganate to the ethanol was 4:1, and the addition ratio of the porous Ti3C2 nanosheets to the ethanol was 0.1g:100mL.

[0075] (4) Preparation of modified composite Ti3C2 lithium battery negative electrode material: The modified porous Ti3C2 material prepared in step (2) and the porous Ti3C2 / MnO2 composite material prepared in step (3) are mixed in a mass ratio of 2:60 to obtain a modified composite Ti3C2 lithium battery negative electrode material.

[0076] The relevant performance tests are as follows:

[0077] 1. The specific surface area, pore volume and interlayer spacing of the lithium battery negative electrode materials prepared in Examples 1-4 and Comparative Examples 1-4 were tested. The test results are shown in Table 1 below.

[0078] Table 1

[0079] Group <![CDATA[Specific surface area (m 2 / g)]]> <![CDATA[Pore volume (cm 3 / g)]]> Interlayer spacing (nm) Example 1 115 0.30 1.8 Example 2 102 0.21 1.7 Example 3 110 0.29 1.8 Example 4 105 0.27 1.8 Comparative Example 1 61 0.05 1.1 Comparative Example 2 70 0.08 1.3 Comparative Example 3 71 0.08 1.3 Comparative Example 4 80 0.11 1.4

[0080] As can be seen from the data in Table 1, the specific surface area, pore volume, and interlayer spacing of the lithium battery negative electrode materials prepared in Examples 1-4 are significantly improved compared to traditional Ti3C2 materials, effectively solving the technical problems of aggregation and stacking between existing Ti3C2 sheets. The Ti3C2 material of Comparative Example 1, the direct addition of MnO2 powder to prepare a porous Ti3C2 / MnO2 composite material in Comparative Example 2, and the use of a one-step temperature-controlled stirring reaction and varying the reaction conditions at each stage in the preparation of the Ti3C2 / MnO2 composite material in Comparative Examples 3 and 4, respectively, show a significant decrease in the specific surface area, pore volume, and interlayer spacing of each group of materials compared to Example 1.

[0081] The lithium battery negative electrode materials prepared in Example 1 and Comparative Examples 1-4 were made into half-cells according to the following steps:

[0082] 8g of lithium battery negative electrode material, 1g of conductive carbon black, 15g of 5% carboxymethyl cellulose and 2.5g of deionized water were stirred and mixed to obtain a slurry. The slurry was coated on a copper foil to make a pole piece. After drying, it was used as an electrode. A lithium sheet was used as a counter electrode, polypropylene (PP) was used as a separator, and a mixture of ethylene carbonate and dimethyl carbonate with a volume ratio of 1:1 was used as an electrolyte to assemble into a half-cell. Ten half-cells were made in each group and tested. The half-cells were tested using a battery testing system with a voltage range of 0.01-3V. The relevant electrochemical performance test results were averaged, as shown in Table 2 below.

[0083] Table 2

[0084]

[0085] As can be seen from the data of Example 1 in Table 2, the modified composite Ti3C2 lithium battery negative electrode material of the present invention has excellent electrochemical properties such as high specific capacity, good rate performance, and high first coulombic efficiency. A comparison of the data of Comparative Examples 2-4 with Example 1 shows that when preparing the porous Ti3C2 / MnO2 composite material, directly adding MnO2 powder, adopting a one-step temperature-controlled stirring reaction, and changing the reaction conditions at each stage all have a significant impact on the electrochemical properties of the resulting porous Ti3C2 / MnO2 composite material.

[0086] Although the present invention has been disclosed above with reference to preferred embodiments, this is not intended to limit the present invention. Any person skilled in the art may make some modifications and improvements without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention shall be based on the definition of the claims.

Claims

1. A method for preparing a modified composite Ti3C2 lithium battery negative electrode material, characterized in that: The steps include: (1) Preparation of porous Ti3C2 nanosheets: Ti3C2 was first prepared by chemical etching, then stirred with tetramethylammonium hydroxide solution, and dried to obtain porous Ti3C2 nanosheets; (2) Preparation of modified porous Ti3C2 material: adding tungsten disulfide powder to a polyethyleneimine aqueous solution, ultrasonicating, centrifuging, and drying to obtain treated tungsten disulfide, and adding the treated tungsten disulfide to water to obtain a tungsten disulfide aqueous solution; adding the Ti3C2 nanosheets obtained in step (1) to the tungsten disulfide aqueous solution, stirring, centrifuging, and drying to obtain a modified porous Ti3C2 material; (3) Preparation of porous Ti3C2 / MnO2 composite material: The porous Ti3C2 nanosheets obtained in step (1) are dispersed in a potassium permanganate aqueous solution in a reactor, ethanol is added to the reactor, and the temperature is raised to 75-100°C for reaction. After the reaction is completed, the reaction product is cleaned by vacuum filtration and dried to obtain a porous Ti3C2 / MnO2 composite material; (4) Preparation of modified composite Ti3C2 lithium battery negative electrode material: The modified porous Ti3C2 material prepared in step (2) is mixed with the porous Ti3C2 / MnO2 composite material prepared in step (3) to obtain a modified composite Ti3C2 lithium battery negative electrode material.

2. The method for preparing a modified composite Ti3C2 lithium battery negative electrode material according to claim 1, characterized in that: Step (1) specifically includes the following steps: adding Ti3AlC2 to an acidic LiF etching solution, heating to 38-45°C, reacting for 20-30 hours, collecting Ti3C2, making Ti3C2 into a suspension, adding a tetramethylammonium hydroxide solution with a mass concentration of 20-30% to the Ti3C2 suspension and stirring, stirring and reacting at 38-45°C for 48-60 hours, collecting and drying to obtain porous Ti3C2 nanosheets.

3. The method for preparing a modified composite Ti3C2 lithium battery negative electrode material according to claim 1, characterized in that: Step (2) specifically includes the following steps: adding 1-2 g of tungsten disulfide powder to 100 mL of a polyethyleneimine aqueous solution with a mass concentration of 1-3%, treating it at an ultrasonic power of 100-150 W for 6-10 hours, centrifuging, and drying to obtain treated tungsten disulfide; adding the treated tungsten dioxide to water and mixing to obtain a tungsten disulfide aqueous solution; adding the Ti3C2 nanosheets obtained in step (1) to the tungsten disulfide aqueous solution, wherein the mass ratio of the Ti3C2 nanosheets to the treated tungsten dioxide is 1-5:2-8; stirring for 5-8 hours, centrifuging, and drying to obtain a modified porous Ti3C2 material.

4. The method for preparing a modified composite Ti3C2 lithium battery negative electrode material according to claim 1, characterized in that: In step (3), the concentration of the potassium permanganate aqueous solution is 4-8wt%, the mass ratio of potassium permanganate to the ethanol is 3.8-4.5:1, and the addition ratio of the porous Ti3C2 nanosheets to the ethanol is 0.05-0.3g:100mL.

5. The method for preparing a modified composite Ti3C2 lithium battery negative electrode material according to claim 1, characterized in that: In step (3), the reaction is carried out in the following three stages: Stage 1: Stirring reaction at 75-80°C for 1-2 hours; The second stage: ultrasonic reaction, power is 300-400w, temperature is 90-100℃, time is 1-2h; The third stage: stirring reaction, the temperature is 80-90℃, and the time is 3-5h.

6. The method for preparing a modified composite Ti3C2 lithium battery negative electrode material according to claim 1, characterized in that: In step (4), the mass ratio of the modified porous Ti3C2 material to the porous Ti3C2 / MnO2 composite material is 1-5:20-80.

7. Use of the modified composite Ti3C2 lithium battery negative electrode material prepared by the preparation method according to any one of claims 1 to 6 in a lithium battery, characterized in that: The modified composite Ti3C2 lithium battery negative electrode material is used as the negative electrode material of the lithium battery.